Electrocardiographic changes associated with SGLT2 inhibitors and non-SGLT2 inhibitors: A multi-center retrospective study - Wu, Victor Chien-Chia; Chiu, Kai-Pin; Wang, Chun-Li; Hsu, Chiu-Yi; Tu, Hui-Tzu; Huang, Yu-Tung; Chang, Chih-Hsiang; Huang, Chien-Hao; Kuo, Chang-Fu; Chen, Shao-Wei; Chu, Pao-Hsien; Chang, Shang-Hung (Frontiers in Cardiovascular Medicine, 2022)
Background: Sodium-glucose co-transporter 2 (SGLT2) inhibitors has been shown with cardiovascular benefit in type 2 diabetes mellitus (T2DM) patients. However, its osmotic diuresis still concern physicians with possible electrolyte imbalance. We therefore aimed to investigate electrocardiographic (ECG) changes associated with SGLT2 inhibitors. Methods: Electronic medical records from Chang Gung Research Database between January 1, 2001 and January 31, 2019 were searched for patients with ECG reports and patients on oral hypoglycemic agent (OHA). We then separate these T2DM patients with EKG into taking either SGLT2 inhibitors or non-SGLT2 inhibitors. We excluded patients with OHA use <28 days, age <18, baseline ECG QTc >500ms, and ECG showing atrial fibrillation or atrial flutter. Propensity score matching (PSM) was performed between groups by age, sex, comorbidities, and medications (including QT prolonging medications). Conditional logistic regression and Firth’s logistic regress for rare events were employed to compare the difference between SGLT2 and non-SGLT2 inhibitor patients. Results: After exclusion criteria and PSM there remained 1,056 patients with ECG on SGLT2 inhibitors and 2,119 patients with ECG on non-SGLT2 inhibitors in the study. There were no differences in PR intervals, QT prolongations by Bazett’s or Fredericia’s formulas, new onset ST-T changes, new onset CRBBB or CLBBB, and ventricular arrhythmia between group of patients on SGLT2 inhibitors and group of patients on non-SGLT2 inhibitors. There were no differences between the two groups in terms of cardiovascular death and sudden cardiac death. In addition, there were no differences between 2 groups in terms of electrolytes. Conclusions: Compared with T2DM patients on non-SGLT2 inhibitors, there were no difference in PR interval, QT interval, ST-T changes, bundle-branch block, or ventricular arrhythmia in the patients on SGLT2 inhibitors. There were no differences in cardiovascular mortality between these two groups. In addition, there were no electrolyte difference between groups. SGLT2 inhibitors appeared to be well-tolerated in terms of cardiovascular safety.